2011
DOI: 10.1176/appi.neuropsych.23.2.132
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Sociopathy in Dementia

Abstract: Although well-known from head trauma and acute strokes, sociopathic behavior from dementia is less known and understood. This study reviewed 33 dementia patients who had been in trouble with the law. They were divided into two groups: 22 who committed impulsive sociopathic acts and 11 who committed non-impulsive acts. The impulsive patients demonstrated nonviolent acts, such as dis-inhibited sexual behavior or pathological stealing, and had disproportionate frontal-caudate atrophy on neuroimaging. The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…Although showing minimal impairments on standard neuropsychological tests of intelligence and executive functions, the subjects show marked deficits in real‐life tasks demanding judgment, awareness of socially appropriate conduct and the capacity to assess future consequences . The occurrence of sociopathy as a manifestation of dementia differs from antisocial/psychopathic personality disorder: a study showed that dementia patients committed sociopathic acts because of disinhibition, and others had sociopathic behavior associated with agitation paranoia, rather than primarily from poor impulse control . In addition, whereas most antisocial behavior committed by psychopathic persons is instrumental towards a goal (for example, increased respect), most antisocial behavior committed by those with acquired sociopathy is a reactive consequence of frustration .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although showing minimal impairments on standard neuropsychological tests of intelligence and executive functions, the subjects show marked deficits in real‐life tasks demanding judgment, awareness of socially appropriate conduct and the capacity to assess future consequences . The occurrence of sociopathy as a manifestation of dementia differs from antisocial/psychopathic personality disorder: a study showed that dementia patients committed sociopathic acts because of disinhibition, and others had sociopathic behavior associated with agitation paranoia, rather than primarily from poor impulse control . In addition, whereas most antisocial behavior committed by psychopathic persons is instrumental towards a goal (for example, increased respect), most antisocial behavior committed by those with acquired sociopathy is a reactive consequence of frustration .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, whereas most antisocial behavior committed by psychopathic persons is instrumental towards a goal (for example, increased respect), most antisocial behavior committed by those with acquired sociopathy is a reactive consequence of frustration . Dementia patients with frontal predominance often react impulsively to tempting environmental situations involving sexual or other objects of interest, without concern for the consequences; in addition, the commonest sociopathic acts in dementia are physical assaults that are sometimes correlated with misperceptions and sometimes with frank delusions . Several studies have reported increased AB in persons suffering from dementia compared with the normal population .…”
Section: Resultsmentioning
confidence: 99%
“…Shoplifting by bvFTD patients is frequently reported. 25 In the present study, bvFTD patients were extremely rare. The rareness of bvFTD patients in this study might cause the scarcity of "shoplifting."…”
Section: Discussionmentioning
confidence: 49%
“…“Shoplifting” and “problems in driving a car” are relatively rare troubles. Shoplifting by bvFTD patients is frequently reported . In the present study, bvFTD patients were extremely rare.…”
Section: Discussionmentioning
confidence: 51%
“…Disinhibition interrupts the ability to suppress automatic behaviours, urges, and emotions and obstructs goal‐directed behaviours such as delaying gratification, resisting temptation, and controlling impulses. Disinhibition is one of the core symptoms that needs to be evident for a diagnosis of bvFTD to be made, and has been linked to behaviours such as impulsivity with excessive spending, onset of gambling, and disinhibited sexual behaviour (Lough, Gregory, & Hodges, ; Manes et al ., ; Mendez, Shapira, & Saul, ). Disinhibition is also well documented in studies of ABI, including promiscuity, excessive eating, and risky decision‐making (Faruqui & Rowell, ; Miller, Cummings, McIntyre, Ebers, & Grode, ; Nakimi et al ., ).…”
Section: A Failure To Control Behaviour: Learning From Reward and Punmentioning
confidence: 99%